Spiritualitas Ina Na Marsahala dan Eksistensi Perempuan Batak - Siagian, Riris Johanna (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2025)
This study examines the concept of Ina na Marsahala as a cultural-theological representation of Batak women’s spirituality and character within the framework of contextual theology. The central research question explores how the values of sahala—understood as the integration of spiritual depth, moral excellence, and personal integrity—are embodied in the lived experiences of Batak women in their families, communities, and church life. The study was conducted in a Batak community in Pematangsiantar and involved nine participants, including two key informants who have long-standing roles in Batak religious and cultural life. Using a qualitative case study approach, data were gathered through Focus Group Discussions (FGDs) and in-depth interviews, then analyzed thematically and validated through triangulation. The research identified six core values that define the Ina na Marsahala identity: Sitiop Puro, Soripada, Parsonduk Bolon, Parsangkalan na so ra mahiang, Partataring na so ra mintop, and Parbahulbahul na Bolon. These values reflect a form of incarnational spirituality and ethical leadership that is deeply rooted in everyday practices. Ultimately, the study concludes that Ina na Marsahala provides a strong theological foundation for contextual feminist theology—one that is both rooted in indigenous wisdom and aligned with the vision of transformative Christian ministry among Batak communities.